2006
DOI: 10.1002/elps.200500785
|View full text |Cite
|
Sign up to set email alerts
|

β‐Actin is not a reliable loading control in Western blot analysis

Abstract: Beta-actin is often used as a loading control in Western blot analysis. We analyzed the ability of beta-actin-specific antibodies to recognize differences in protein loading. We found that, at higher total protein loads as required for the detection of low-abundance proteins, beta-actin-specific antibodies failed to distinguish differences in actin protein levels. Diluting the antibody working solution or changing the incubation time had little effect on this phenomenon. This shows that beta-Actin is not a rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(141 citation statements)
references
References 4 publications
5
130
2
2
Order By: Relevance
“…Antibodies recognizing nuclear factor of activated T cells 1 (NFAT-1), Ets1, or extracellular signal-regulated kinase 1/2 (ERK1/2) were from BD Transduction Laboratories (1:2,500), Santa Cruz Biotechnology, Inc. (C20, 1:2,000), or Cell Signaling (1:1,000), respectively. GAPDH-specific (1:5,000; Ambion) and ERK1/2-specific antibodies were used to check for equal protein loading (25). As GAPDH is also abundant in the nucleus (26), we used the GAPDHspecific antibody also to control protein loading of nuclear extracts.…”
Section: Methodsmentioning
confidence: 99%
“…Antibodies recognizing nuclear factor of activated T cells 1 (NFAT-1), Ets1, or extracellular signal-regulated kinase 1/2 (ERK1/2) were from BD Transduction Laboratories (1:2,500), Santa Cruz Biotechnology, Inc. (C20, 1:2,000), or Cell Signaling (1:1,000), respectively. GAPDH-specific (1:5,000; Ambion) and ERK1/2-specific antibodies were used to check for equal protein loading (25). As GAPDH is also abundant in the nucleus (26), we used the GAPDHspecific antibody also to control protein loading of nuclear extracts.…”
Section: Methodsmentioning
confidence: 99%
“…The bands were quantified by mean optical density using computer-assisted densitometry with ImageJ v1.41 (National Institutes of Health, USA). As loading controls (eg, actin and GAPDH) often used for in western blot experiments are subject to quantitation errors (Aldridge et al, 2008;Dittmer and Dittmer, 2006), each gel was normalized to a total protein stain (Swift stain; G-Biosciences, St Louis, MO). Before each study, a series of western blottings were performed using different titrations of sample and antibody, to establish the linear range for each response.…”
Section: Western Blottingmentioning
confidence: 99%
“…Unfortunately, this discrepancy in protein abundance between POI and the LC means that homogenate concentrations that allow the POI to be in the linear range of detection on a polyacrylamide gel, necessarily put the LC outside the linear range of detection. Recently it was shown that β-actin is a poor control for many Western blot analyses because at the protein concentrations most often used, optical density values are not only outside the linear range, but they become essentially uncorrelated with protein concentration (Dittmer and Dittmer, 2006). This second issue is pertinent even in the case of qualitative studies, where loading controls are just compared visually, because such studies often assume that if the protein bands appear to be equal, they must be very nearly so.…”
Section: Introductionmentioning
confidence: 99%